(untitled) (Jurnal Manajemen Bisnis, 2026)
This study aimed to examine the influence of technical analysis and corporate social responsibility (CSR) on the firm value of PT. Bank Rakyat Indonesia (Persero) Tbk. A quantitative approach was employed, utilizing a survey method with questionnaires distributed to the employee population. The sampling technique was saturated sampling, and the data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The measurement model evaluation confirmed the reliability and validity of the constructs, while the structural model demonstrated a satisfactory fit and substantial explanatory power. The results revealed that both technical analysis and corporate social responsibility had a positive but statistically insignificant effect on firm value at the standard significance level. However, the structural model explained a high degree of variance, indicating that these variables collectively provide a strong framework for firm value. These findings suggest that while individual strategies may not directly drive firm value independently, their collective presence provides a robust framework for market perception. The implication is that companies should focus on a strategic synergy between technical market approaches and CSR programs to build sustainable corporate value.